Analysis of Drilling of Coir Fiber-Reinforced Polyester Composites Using Multifaceted Drill Bit - T. V. Rajamurugan; C. Rajaganapathy; S. P. Jani; Claris Snigdha Gurram; Haiter Lenin Allasi; Samson Zerihun Damtew (Advances in Materials Science and Engineering)
Composite materials are continuously replacing the conventional materials and alloys owing to their weight reduction. Biodegradable fiber-reinforced composite materials are one of the prime attractions to the researcher due to their easy availability and low cost. During drilling of these Natural Fiber Reinforced Plastic composites (NFRP), delamination and surface roughness are the problems encountered, which are to be minimized to get better output by adopting different cutting conditions and tools. This work aims at the drilling of naturally available coir fiber-reinforced composite materials by using a multifaceted drill bit. Material thickness, spindle speed, feed rate, and multifaceted bit diameter are input against the output delamination. After modeling of the output result, a sensitivity analysis tool is introduced to rate the input factor to minimize delamination. SEM images are used to analyze the fracture morphology.